Continuability of Lienard’s Type System with Generalized Local Derivative - Chatzarakis, George E.; Valdés, Juan E. Nápoles (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we study the boundedness and continuability of the solutions of a generalized Liénard type system, using fractional derivatives of the local type. We obtain sufficient conditions for the solutions to be bounded and continuous by a suitably defined Lyapunov function. We illustrate the results and suggest extensions to asymptotic stability, through various examples adapted from the relevant literature.